Alternative Sanctions in Islam (Foundational Study) - Yaser Esayed Fujo (الإيضاح, 2023)
The Islamic legislation comprises of Hudud (mandatory rulings with no scope for rational judgment/Ijtihad) and Ta'zir penalties (discretionary rulings such as imprisonment and financial fines. This article is based on a jurisprudential discussion about the alternative sanctions in Islam.